Experimental Study on the Effect of Moisture on Bolt Embedment and Connection Loaded Parallel to Grain for Timber Structures - Kiwelu, Henry M. (Tanzania Journal of Engineering and Technology, 2019)
Connections are critical parts of timber structures, transmitting static and dynamic forces between structural elements. The ultimate behaviour of a building depends strongly on the structural configuration and the capacity of its connections. The complete collapse of a building or other less extensive accidents that may occur usually start as a local failure inside or in the vicinity of a joint. The main aim of this study has been to investigate if the short-term capacity of steel-wood dowel joints loaded parallel to the grain is affected by variations in moisture content associated with post fabrication drying or wetting of the timber. Extensive experiments were conducted. The experimental results showed that the stiffness and load-bearing capacity of the joints is reduced by post-fabrication wetting and is increased by post-fabrication drying. It was clear from those test results that changes in mechanical properties were greater than could be explained by effects moisture content changes have on material properties, implying that simple adjustments of properties in that way for purposes of structural design are unreliable Currently in the design of timber connection in code of practise is the effect of variation of moisture is not considered. The results revealed that there is a great effect on timber performance which is due to an increase of moisture content. Keywords: Beam, creep, wood, heat transfer, hydrothermal strain, moisture strain.